A study of the mediating role of self-esteem between parent-child relationship and psychological distress among undergraduate students in Malaysia - Wan, Kimberly Jia Xian; Mak, Wei Teng (2023)
The parent-child relationship is a prevalent topic, and it greatly influences a child's mental development. The quality of the parent-child relationship is linked to psychological distress and self-esteem. Therefore, the present study aims to investigate the mediating effect of self-esteem between parent-child relationships and psychological distress among undergraduate students in Malaysia. This study used a quantitative research design to collect and analyze data. A total of 158 participants were recruited through purposive sampling on social media platforms such as Facebook, LinkedIn, WhatsApp, Xiaohongshu, and Microsoft Teams. The data were collected online using the Qualtrics questionnaire survey form. All 158 participants completed the survey and fulfilled the inclusion criteria of (i) Malaysian nationality, (ii) young adults aged between 18 and 24 years, and (iii) currently enrolled in undergraduate studies in Malaysia. The Inventory of Parents and Peer Attachment, Rosenberg Self-Esteem Scale, and Kessler Psychological Distress Scale were employed to assess relevant variables. Ethical considerations were addressed before distributing the online questionnaire, ensuring participants' voluntary and confidential participation. The results indicated significant associations between parent-child relationships and both psychological distress and self-esteem. A notable correlation between psychological distress and self-esteem was identified. The study emphasized the mediating role of self-esteem in the parent-child relationship and psychological distress. These findings align with previous research and provide valuable insights for future studies. The study’s implications offer a reference point for subsequent research. Overall, this research helps us understand the intricate relationship between parents and children, self-esteem, and psychological well-being among Malaysian undergraduates